State, Trends and Normative Regulation of Cybercrime in the Republic of Croatia - Kondor-Langer, Mirjana; Borovec, Krunoslav; Gluščić, Stjepan (Kriminalističke teme, 2019)
The inspiration for the paper and the problem (s) that the paper addresses: The first part of the paper gives an analysis of the provisions of the Criminal Code of the Republic of Croatia. Furthermore, the paper presents data on the reported and re-solved computer crime according to official statistics and the results of the conducted research on computer crime awareness. The goals of the paper (scientific and/or social): The research goals sought to deter-mine youth habits related to Internet use; examine their awareness and experience of the dangers of cybercrime; determine the level of cybercrime victimization and deter-mine if there is a link between negative experiences on the internet and any possible victimization with behavior change when using the internet. Methodology/Design: The research sample included a convenience sample of 344 respondents, students of polytechnics and colleges in the Republic of Croatia. The results obtained by this research were analyzed in the SPSS statistical program. The paper presents the results of descriptive statistics and the marginal frequency of respondents’ answers to a particular question. Two tests were used to determine whether there are links between negative experiences on the Internet and possible victimization with behavioral change when using the Internet- the chi-square test and the test of the independence of two variables. Research/the paper limitations: The limitations of this research are reflected in fact that the respondents are only students from Croatian Colleges whose behaviors and experiences related to the use of Internet cannot be generalized to the general population. Therefore, the obtained results should be viewed in the context of these limitations. On the other hand, reported and discovered crimes data were collected from official police database and they do not present total but only registered crime. Results/findings: The conducted research showed that 46.8% of the respondents were constantly on the Internet. 54.9% of them do not consider their information on the internet to be secure, and 18.4% of the respondents were victims of cybercrime. General conclusion: The conducted research showed a high level of success in resolving reported crime and a high level of awareness of the dangers of new technologies, but it also drew attention to the inadequate level of cybersecurity. Research/the paper justifiability: Computer crime in the Republic of Croatia is an important area for the police. Significant progress can be made in this area by strengthening prevention and by working with potential victims. That would create trust between police and citizens (where it does not exist), remove obstacles to reporting crimes and facilitate cooperation during the investigation of those types of crime.